Assessment of acid resistance of natural pozzolan-based alkali-activated concrete: Experimental and optimization modelling. (18th October 2021) - Ibrahim, Mohammed; Salami, Babatunde Abiodun; Amer Algaifi, Hassan; Kalimur Rahman, Muhammed; Nasir, Muhammad; Ewebajo, Adeoluwa Oladapo
Highlights: Acid resistance of NP/nSiO2 -based AAC exposed to 5% H2 SO4 was evaluated. Visual examination, weight loss, reduction in strength and micro analytical changes to the binder were studied. nSiO2 addition significantly improved the performance of AAC compared to control and OPC. Gypsum formation was confirmed in the binder prepared with 0–2.5% nSiO2 and OPC. Al, Ca, and Na were eliminated from the binder structure upon exposure to acid. Due to stable cross-linked C-A-S-H structure, 5% and 7.5% nSiO2 modified binder performed considerably better. Abstract: Although the synthesis and properties of natural pozzolan (NP)-based alkali-activated binder (AAB) have been investigated, to the best of our knowledge, no study has focused on and assessed the performance of such concrete when exposed to acid attack. In addition, there is a lack of information regarding the optimisation of reaction parameters. Therefore, in the present study, NPs blended with nano-silica (nSiO2 ) from 0 to 7.5% were taken into account to develop alkali-activated concrete (ACC), cured at room temperature, and subsequently exposed to 5% sulfuric acid (H2 SO4aq ). The performance of the NP/nSiO2 -based ACC was evaluated by visual examination, microstructure, weight loss, and compressive strength loss up to one year of exposure to an acidic environment. In addition, artificial neural network (ANN) and response surface methodology (RSM) models were developed to predict and optimize nSiO2 to ascertain the minimum weight and strength loss. Based on both the predicted and actual results, a significant improvement in the microstructure was achieved with an increase in nSiO2 . The micro-analytical examination revealed the leaching of vital elements from the binder structure, such as Al, Ca, and Na, which enabled the creation of highly expansive substances such as gypsum, which caused cracking and eventually disintegration in the OPC and NP-based AAB incorporating lower quantities of nSiO2 . Both the loss in weight and strength were in the range of 23%–39% in the 1% to 7.5% nSiO2 modified AAC. In contrast, in the control AAC and OPC-based concrete, a weight loss of more than 50% was recorded, along with a substantial reduction in strength.